Pelaksanaan Gotong Royong Dalam Meningkatkan Perilaku Hidup Bersih Di Kelurahan Pematang Gubernur: KKN-T Unived 2025 - Lestari, Anggun Ayu; Oktafia, Berliana; Illahi, Jerry Kurnia; Sadewo, Panji; Qhumayira, Tharisa; Hanila, Siti; Susena, Karona Cahya; Suwarni, Suwarni (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
The Thematic Community Service Program (KKN-T) of Dehasen University Bengkulu Group 12 in 2025 was held in RT007/RW04 Pematang Gubernur Village, Muara Bangkahulu District, Bengkulu City, from June 11 to July 4, 2025. This program aims to improve clean living behavior and strengthen mutual cooperation in the community. The main problem faced is the low level of public awareness in littering, which results in a dirty environment and clogged gutters, especially during the rainy season. The methods used include initial observation, socialization, direct implementation, and assistance in environmental cleanliness mutual cooperation activities. KKN-T students together with local officials were actively involved in cleaning yards, public roads, gutters from garbage and weeds. The results of the activity showed an increase in community participation and awareness of the importance of maintaining cleanliness and preserving the culture of mutual cooperation. It is hoped that this activity can create a clean, healthy, beautiful environment, and free from disease and flood disasters, as well as strengthen the sense of ownership and responsibility of the community towards their environment.